From Self Banishing Life to Life Banishing Self: The Prominent Causality and Lady Macbeths Tragic Downfall - Uddin, Md Abu Saleh Nizam (IIUC Studies, 2016)
Lady Macbeth of Macbeth is one of the most widely discussed characters created by Shakespeare. In the drama, just after Macbeth's disclosure to her as regards the witches' prophecy, she decides to pursue the shortest way to reach her goal within the shortest possible time. She instantly plans to kill King Duncan to enable Macbeth to ascend the Scottish throne. In this process she ultimately plans to have her share in power and prestige with her husband. To prepare herself for the horrible act of the murder, Lady Macbeth completely rejects natural and vital contents and functions of her soul or self. It is the dreadful banishment of self from life. It is tantamount to a manifold distortion of her feminine and human soul. She succeeds in her attempt only to experience the unbearable weight of regret and remorse that finally causes her to punish herself terribly in her own morose conditions which is lifes banishment from self, a downfall of colossal magnitude. This article aims at understanding the significance of this issue by studying the functioning of Lady Macbeths soul from the perspective of philosophy. This will also be done and by juxtaposing her with characters of similar nature from some of the great literary works. IIUC Studies Vol.10 & 11 December 2014: 217-230